Anti-Psl Targeting of Pseudomonas aeruginosa Biofilms for Neutrophil-Mediated Disruption. Issue 1 (December 2017) - Ray, Valerie; Hill, Preston; Stover, C.; Roy, Sashwati; Sen, Chandan; Yu, Li; Wozniak, Daniel; DiGiandomenico, Antonio
Abstract Bacterial biofilms are recalcitrant to antibiotic therapy and a major cause of persistent and recurrent infections. New antibody-based therapies may offer potential to target biofilm specific components for host-cell mediated bacterial clearance. ForPseudomonas aeruginosa, human monoclonal antibodies (mAbs) targeting the Psl biofilm exopolysaccharide exhibit protective activity against planktonic bacteria in acute infection models. However, anti-Psl mAb activity againstP .aeruginosa biofilms is unknown. Here, we demonstrate that anti-Psl mAbs targeting three distinct Psl epitopes exhibit stratified binding in maturein vitro biofilms and bind Psl within the context of a chronic biofilm infection. These mAbs also exhibit differential abilities to inhibit early biofilm events and reduce biomass from mature biofilms in the presence of neutrophils. Importantly, a mAb mixture with neutrophils exhibited the greatest biomass reduction, which was further enhanced when combined with meropenem, a common anti-Pseudomonal carbapenem antibiotic. Moreover, neutrophil-mediated killing of biofilm bacteria correlated with the evident mAb epitope stratification within the biofilm. Overall, our results suggest that anti-Psl mAbs might be promising candidates for adjunctive use with antibiotics to inhibit/disruptP .aeruginosa biofilms as a result of chronic infection.